Multiple-quantum 27Al MAS NMR spectroscopy of microporous AlPO-40 and SAPO-40 - Rocha, J. (2013)
Two-dimensional triple- and quintuple-quantum 27AI magic-angle spinning (MO MAS) n.m.r. spectra of microporous AIPO-40 and SAPOBO have been recorded at 9.4 and 14.1 T. The resolution of the 5Q spectra of AIPO-40 is amazing, at least 11 resonances being resolved. The 3lQ spectra further reveal the presence of 2 other much fainter peaks. Because the AIPO-40 aluminium sites have different quadrupole coupling constants the 9.4 T spectra are slightly better resolved than the 14.1 T spectra, suggesting that in MO n.m.r. it may sometimes be advantageous to work at lower magnetic fields. The 3Q spectra of SAPO-40 are poorly resolved displaying a main broad peak and two faint resonances. This is because the introduction of even a small amount of Si into the framework of AIPO-40 generates a distribution of Al sites and a dispersion of chemical shifts. MQ 27AI MAS n.m.r. together with 31P MAS n.m.r. evidence discard an orthorhombic, Pccn, and monoclinic, P172/n, structure for as-prepared or calcined dehydrated AIPO-40, suggesting a space group with even lower symmetry that proposed to date.